Bioassay-guided isolation of sesamin and fargesin from the hydroalcoholic stem extract of Zanthoxylum armatum DC. inhibited inflammation in CpG-stimulated conventional type 1 dendritic cells - Singh, Ningthoujam Indrajit; Mukherjee, Chayan; Soibam, Jerina; Singh, Wangkheimayum Marjit; Bal, Naresh Chandra; Raghav, Sunil Kumar; Singh, Chingakham Brajakishor (Frontiers in Pharmacology, 2025)
IntroductionZanthoxylum armatum DC. is renowned for its medicinal values. All the plant parts have been used to treat tooth- and gum-related problems, gastro-intestinal problems, inflammation, rheumatism, and pain by the indigenous people of Nepal, India, China, and other South East Asian countries. Bioassay-guided isolation of active compounds from medicinal plants is recognized as a promising approach for the discovery of novel drug candidates. The objective of this study was to examine the main constituents of Zanthoxylum armatum DC. stems through bio-guided isolation and to explore their anti-inflammatory potential.MethodSequential fractions were prepared from the hydromethanolic stem extract of Z. armatum DC. Afterward, bioassay-guided isolation was conducted using a combination of column chromatography, heat-induced hemolysis inhibition assay, and albumin denaturation inhibition assay. The structures of the isolated compounds were elucidated through single crystal XRD and NMR. The anti-inflammatory activity of the compounds was evaluated in vitro by measuring the expression levels of IL12 and CD80 using flow cytometry.ResultsSequential ethyl acetate fraction showed the highest protein anti-denaturation and membrane stabilization activities. Afterward, sesamin and fargesin were isolated from the sequential ethyl acetate fraction. Both of them showed activity against IL12 production by conventional type 1 dendritic cells. Moreover, fargesin significantly inhibited the expression of CD80.ConclusionThe results identified bioactive compounds with potential against the pro-inflammatory dendritic cells for the first time. The findings justified the traditional use of Z. armatum DC. as an anti-inflammatory agent.